Womenomics and Japan’s Domestic Politics: The Transformation of Women Roles in the Shinzo Abe Administration - Dharma, Nathania Yunita; Simanjuntak, Triesanto Romulo; Hergianasari, Putri (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
The issue of gender inequality is one of the big problems that Japan is facing nowadays. In the annual survey of the Women Economic Forum, Japan often occupies the lowest position in the indicators of women's participation in politics. This issue became one of Shinzo Abe's priorities when he was elected Prime Minister in 2012. Through a major policy during his administration known as Abenomics, Shinzo Abe introduced Womenomics as a gender-based policy strategy to increase women's participation in the workforce, including in politics. Womenomics was developed into several policies that are expected to provide a sense of security for women to be involved in politics so that women's participation rates were expected to increase. This article examines the implementation of Womenomics on women's participation in Japanese domestic politics from 2013 to 2020. It employs the qualitative approach and uses liberal feminism theory as its analytical framework. The data used in this study were secondarily obtained from various sources of books and publications by the Japanese government.